FORMULATING BUSINESS STRATEGY AND PROFITABILITY TO INCREASE COMPANY VALUE: AN ANALYSIS OF THE MEDIATING ROLE OF CORPORATE SOCIAL RESPONSIBILITY - Erlita; Arry Widodo; Putu Nina Madiawati (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of business strategy and profitability on firm value, with Corporate Social Responsibility (CSR) as a mediating variable at Bank BPD DIY. This study uses a quantitative causality approach with a confirmatory nature, testing the extent to which the Resource-Based View (RBV) and Stakeholder Theory are confirmed in the context of the regional banking industry. Primary data were collected through a 1–5 Likert-scale questionnaire from all BPD DIY managers (census method, 163 respondents) who met the criteria of managerial position, minimum three years of service, and involvement in strategic policy. Data analysis was performed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of SmartPLS. This involved testing the outer model (convergent validity, discriminant validity, reliability) and inner model (path coefficient, R², f², Q²) to assess the direct and indirect effects between variables. The variables studied included business strategy, profitability, CSR, and firm value, operationalized across several dimensions, including future orientation, operational efficiency, the social and environmental dimensions of CSR, and market value and corporate reputation. The instrument was independently developed based on theoretical synthesis (David & David, Houston, Teodorescu Ionescu, Carroll, and others), then validated through expert judgment before being tested for validity and reliability on pilot respondents. The results showed that business strategy had a positive effect on CSR and firm value, while profitability had a positive effect on CSR and firm value, aligning with the view that slack resources and a prospector strategy encourage stronger CSR activities and improved market perception. CSR was shown to have a positive effect on firm value and acted as a mediating variable in the relationships between business strategy and firm value and profitability and firm value. Thus, CSR implementation strengthens the transmission of the influence of strategy and financial performance on increasing firm value. These findings confirm that the integration of a sustainability-oriented business strategy, strong profitability performance, and consistent CSR implementation is a crucial combination for enhancing firm value in the regional banking sector.